CURRENT STATUS AND FACTORS INFLUENCING NURSES' ORGANIZATIONAL COMMITMENT AT BINH DUONG GENERAL HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the level of organizational commitment and identify factors influencing nurses’ engagement at Binh Duong General Hospital in 2024.Methods: A cross-sectional mixed-method study was conducted from April to December 2024. Quantitative data were collected from 101 nurses across 20 clinical departments using a 5-point Likert scale adapted from Tran Kim Dung’s (2006) OCS. Qualitative data were obtained through 15 in-depth interviews and 4 focus group discussions with hospital leaders, head nurses, and nurses.Results: The overall mean score was 3.75 ± 0.51, indicating a fairly high level of commitment. Among the three components, “loyalty” had the highest mean score (3.78 ± 0.61). Statistically significant factors associated with organizational commitment included gender, educational level, and opportunities for promotion (p < 0.05). Qualitative findings revealed that low income, limited rewards, heavy workload, and insufficient opportunities for career advancement were major barriers affecting nurses’ engagement with the hospital.Conclusion: To enhance commitment, the hospital should improve compensation and incentive policies, expand training and promotion opportunities, and foster a supportive organizational culture. Strengthening managerial capacity and promoting effective communication between leaders and staff are also essential to retain the nursing workforce under the financial autonomy mechanism.
Keywords: nurses, organizational commitment, public hospital, general hospital.